(untitled) (Al-Qamar, 2025)
This research explores the theological discussions in Tajuman-ul-Quran, a famous Quranic commentary by Maulana Abul Kalam Azad. It examines how Maulana Azad explained Islamic beliefs using simple yet meaningful arguments, connecting traditional ideas with modern thoughts. The study highlights how his work addresses key topics like Tawhid (belief in one God), Nubuwwat (prophethood), Akhirat (afterlife), and the creation of the universe. Maulana Azad’s approach combines reasoning and faith, making Quranic teachings understandable for everyone. His language is clear and effective, helping readers from all backgrounds engage with the Quran’s message. The research also shows how Tajuman-ul-Quran is not just a religious text but a guide for solving modern issues while staying true to Islamic values. This study concludes that Maulana Azad’s Tajuman-ul-Quran is a timeless work, offering valuable insights for understanding faith in a way that connects with both tradition and today’s world. It highlights the importance of his efforts in making the Quran’s message accessible to people of all intellectual levels. By bridging the gap between classical interpretations and contemporary needs, Maulana Azad has shown how the Quran can guide humanity in addressing ethical, spiritual, and intellectual challenges. His work serves as a source of inspiration for those seeking to balance faith with reason, and tradition with progress, making Tajuman-ul-Quran a masterpiece of enduring relevance in Islamic scholarship.